2020
DOI: 10.3390/cryst10121075
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding in the Complexes of Brominated Electrophiles with Chloride Anions: From a Weak Supramolecular Interaction to a Covalent Br–Cl Bond

Abstract: The wide-range variation of the strength of halogen bonds (XB) not only facilitates a variety of applications of this interaction, but it also allows examining the relation (and interconversion) between supramolecular and covalent bonding. Herein, the Br…Cl halogen bonding in a series of complexes of bromosubstituted electrophiles (R-Br) with chloride anions were examined via X-ray crystallographic and computational methods. Six co-crystals showing such bonding were prepared by evaporation of solutions of R-Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…The M062X/6-311+G(d,p) method was used in our earlier computations of XB complexes. 12 15 Previous theoretical analyses indicated that it produces excellent geometries and energies at a reasonable computational cost. 34 , 35 Importantly, our earlier studies demonstrated that the characteristics of the XB complexes between RBr electrophiles obtained via such computations were in good agreement with the experimental data.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The M062X/6-311+G(d,p) method was used in our earlier computations of XB complexes. 12 15 Previous theoretical analyses indicated that it produces excellent geometries and energies at a reasonable computational cost. 34 , 35 Importantly, our earlier studies demonstrated that the characteristics of the XB complexes between RBr electrophiles obtained via such computations were in good agreement with the experimental data.…”
Section: Methodsmentioning
confidence: 99%
“… 36 This moderately polar solvent represents a good media for modeling solid-state ionic compounds. 14 , 15 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations